Vaccine Hesitancy in Children-A Call for Action - Annabelle de St. Maurice; Kathryn M. Edwards (MDPI AG, 2016)
Immunizations have made an enormous impact on the health of children by decreasing childhood morbidity and mortality from a variety of vaccine-preventable diseases worldwide. The eradication of polio from Nigeria and India is one of the most recent victories for one of the greatest technological advances in human history. Despite these international successes, the United States has experienced the re-emergence of measles, driven largely by increasing parental refusal of vaccines. Pediatricians should be trained to be very knowledgeable about vaccines and should continue to advocate for parents to immunize their children.